2016
DOI: 10.1042/bst20160034
|View full text |Cite
|
Sign up to set email alerts
|

How myosin organization of the actin cytoskeleton contributes to the cancer phenotype

Abstract: The human genome contains 39 genes that encode myosin heavy chains, classified on the basis of their sequence similarity into 12 classes. Most cells express at least 12 different genes, from at least 8 different classes, which are typically composed of several class 1 genes, at least one class 2 gene, and classes 5, 6, 9, 10, 18 and 19. While the different myosin isoforms all have specific and non-overlapping roles in the cell, in combination they all contribute to the organisation of the actin cytoskeleton, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 109 publications
1
24
0
Order By: Relevance
“…Modifications of the actin cytoskeleton during the metastatic process are well described (Vignjevic & Montagnac, 2008;Nürnberg et al, 2011;Peckham, 2016). Notably the relative amount of filamentous actin (F-actin) and monomeric actin (G-actin), which indicates the level of actin polymerisation, depends on the cell malignancy.…”
Section: Actinmentioning
confidence: 99%
“…Modifications of the actin cytoskeleton during the metastatic process are well described (Vignjevic & Montagnac, 2008;Nürnberg et al, 2011;Peckham, 2016). Notably the relative amount of filamentous actin (F-actin) and monomeric actin (G-actin), which indicates the level of actin polymerisation, depends on the cell malignancy.…”
Section: Actinmentioning
confidence: 99%
“…This property first appeared in ancient MyTH4-FERM myosins and is conserved over 1 billion y of evolution (14,16,17). Mutations of MyTH4-FERM myosins cause a broad spectrum of human diseases, including hearing loss, vision defects, digestive disorders, and cancers (18)(19)(20)(21), often because of defects in actin bundle-supported protrusions (i.e., filopodia, microvilli, or stereocilia). The specific functions of Myo7a, Myo7b, Myo10, and Myo15a in regulating actin-bundle protrusion structures in various tissues must be a result of, at least in part, the unique cargo binding properties of their MyTH4-FERM domains.…”
mentioning
confidence: 99%
“…GO and KEGG pathway enrichment analysis shows that these PMPs were mainly enriched in actin lament organization. Studies have found that actin lament organization plays a role in a variety of tumors such as prostate cancer, head and neck cancers and melanomas [11]. However, there is no reports about actin lament organization in renal cancer, further experimental exploration is needed in the future.…”
Section: Discussionmentioning
confidence: 99%